Baclofen in alcohol use disorder: An analysis of the data provided by the French “Temporary Recommendation for Use” 2014–2017 cohort - de Beaurepaire, Renaud; Rolland, Benjamin (Frontiers in Psychiatry, 2022)
Alcohol use disorder (AUD) is a devastating illness for which effective treatments are lacking. Studies over the last two decades have shown that baclofen, a GABA-B agonist, could be a promising treatment for AUD. However, the efficacy of baclofen is still controversial, and studies have shown that it may be associated with an excess of hospitalizations and deaths. In March 2014, the French Health Safety Agency granted a “Temporary Recommendation for Use” (TRU) regulating the prescription of baclofen in subjects with AUD. The TRU allowed physicians to prescribe high-dose baclofen (up to 300 mg/d). The doses were adjusted, and tailored to the needs of each patient. Between March 2014 and March 2017, TRU clinical data were collected for a total of 6,939 subjects. The recorded data included information on alcohol consumption, the intensity of alcohol cravings, and adverse events. The present article proposes an analysis of the data provided by the TRU. Subjects for which data were missing regarding baclofen daily dosage, alcohol consumption or craving scores were discarded from the analyses. A cohort of two groups of subjects was analyzed. The first group included all TRU subjects suitable for analyses (5,550 subjects), and the second group included subjects followed for at least 365 days (169 subjects). Comparisons were made between baseline and endpoint of the follow-up period. The results show that a majority of subjects in the whole cohort had received doses of over 80 mg/d. The mean dose of baclofen at the endpoint was >110 mg/d in the second group of subjects. Doses of >80 mg/d were not associated with an increase in adverse events after adjustment for the follow-up duration. In terms of efficacy, comparisons between baseline and endpoint show that baclofen treatment significantly decreased alcohol consumption and alcohol cravings, and significantly increased the number of subjects with null or low-risk alcohol consumption according to WHO criteria.